FORMAÇÃO INICIAL DO COORDENADOR PEDAGÓGICO: O EGRESSO (2007 – 2010) DA LICENCIATURA EM PEDAGOGIA DA UNIVERSIDADE ESTADUAL DE PONTA GROSSA- PR - Kailer, Priscila Gabriele da Luz (2016)
This study has as object the initial education of the pedagogical coordinator of Ponta Grossa State University between 2007 and 2010. The analysis of the initial education of the pedagogical coordinator is justified due to the historical and social changes held in the locus of the pedagogical coordinator education in recent years. The central question that guided this research was: What are the contributions of the initial education of the Pedagogy course in Ponta Grossa State University (2007-2010) when building the knowledge required to the pedagogical coordinator practice? To this end, the aim of this work was: a) analyze the initial education knowledge of the Pedagogy course of Ponta Grossa State University (2007-2010) that are present in the practice of the pedagogical coordinator; b) investigate the contributions of the initial education of the Pedagogy course of Ponta Grossa State University (2007-2010) when building the knowledge required to the pedagogical coordinator practice. We understand the pedagogical coordinator as part of the teaching staff that does his/her work in the pedagogical coordination and organization of the school. Among the duties of the pedagogical coordinator, we emphasize the activities that involve the continuing education of teachers and mediation for collective construction and implementation of the Pedagogical Master Plan, among other actions whose purpose is students’ learning. We present throughout this text discussions that involve the object of this research, the initial education of the pedagogical coordinator between 2007 and 2010. Therefore, we use the following authors to understand the historical background and the education models of this professional: Kuenzer (1996, 1998, 2002, 2004, 2006), Ferreira (1999, 2003, 2005, 2011) and Saviani (1999, 2002, 2007, 2008). To address the concern about the performance of the pedagogical coordinator and the specific knowledge of this professional, we bring Domingues (2014), Gauthier, (1998), Tardif, (2002) and Pinto (2011). We also discuss the complex relationship between theory and practice that involves the education of the pedagogical coordinator with the following authors: Gimeno Sacristán (1999), Vázquez (1968) and the consensus and dissent that permeated the disputes in the elaboration of the National Curriculum Guidelines of the Pedagogy Course. We discuss the initial education of the teacher of Ponta Grossa State University (2007-2010) in order to understand the education of the pedagogical coordinator in space/time where this work was conducted based on Santos (1999), Masson and Mainardes, (2009). To this end, it was necessary to analyze the design and redesign of the Pedagogical Master Plan of the State University of Ponta Grossa - PR (2007-2010). This research relied on the qualitative approach according to Richardson et al. (1999). Research data were obtained through semi-structured interviews and the document analysis was based on Lüdke e André (1986). The research had the participation of six (6) 2007 and 2010 graduated pedagogical coordinators of the Pedagogy course of the State University of Ponta Grossa. We emphasize that of the six (6) pedagogical coordinators, three (3) worked in the Municipal Center for Early Childhood Education, and three (3) were in the Elementary School. For data analysis, we used Bardin's content analysis (1977). The results of this research show that the amplitude of the education of the pedagogical coordinator defies the possibilities of educating a professional for various functions, teacher, manager and researcher, who, though related, has specificities. We also highlight that the initial education of the Pedagogy course of Ponta Grossa State University (2007-2010) is more focused on teaching, being, consequently, knowledge of the pedagogical coordinator education of secondary importance.